COMPETITIVENESS OF BUSINESS STRUCTURES AS A MANAGEMENT OBJECT: EVOLUTION OF METHODOLOGICAL APPROACHES - MYKHALCHUK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article provides arguments in favor of the fact that a clear understanding by the management of the essence of the competitiveness of the enterprise as an object of management is important for making a well-founded choice of the strategy of the business entity’s behavior on the market. Therefore, the aim of the work is a comparative analysis of methodological approaches to the interpretation of the term "enterprise competitiveness" from the point of view of the correspondence of their essential content to the modern realities of entrepreneurial activity. It is assumed that this will enable the managers of domestic business structures to identify priority areas of management efforts to preserve (restore) their viability in the conditions of economic instability caused by the war and the uncertainty of post-war recovery processes. In the course of the analysis, complex and relative approaches, resource-oriented, competence-targeted and value-oriented are highlighted. The features of each of the approaches and the conditions for their effective application are characterized. It is argued that in the conditions of turbulence and economic instability caused by the war and the uncertainty of future political processes, it is advisable to rely on a value-oriented approach in the management of competitiveness. In the context of this approach, the leading role of information support in the process of creating new value propositions was noted and a logical scheme of this process was developed. Considering the fact that the creation of new consumer values functionally belongs to the subsystems of marketing and innovation management, their specific role in this process is highlighted.